Current status of research on seminal plasma proteins - KULKARNI, B A (The Indian Journal of Animal Reproduction, 2023)
Seminal plasma is a highly complex biological fluid containing proteins, amino acids, enzymes, hormones, carbohydrates, lipids, major minerals and trace elements. During the past two decades several novel seminal plasma proteins viz. forward motility protein (FMP), IgG-Fe binding protein, immobilin, cellular retinal-binding protein (CrBP) androgen-binding protein (ABP), transferrin, seminalplasmin, inhibin, clusterin, calcemin, ferrisplan, gossact, heparin-binding (HBPs), osteopontin, acrosome reaction potentiating protein and BSP proteins BSP-Al’ BSP-A2, BSP-A3 and BSP-30 kDa proteins have been reported. These proteins are synthesized and secreted by various reproductive organs such as the testis, epididymis, ampullae of the vas deferens, seminal vesicles, prostate, and bulbouretheral glands. The origin, tissue localization, isolation, purification, characterization and the potential role of some of these proteins in the biology of reproduction is discussed briefly.